2010
DOI: 10.1016/s1684-1182(10)60060-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and Risk Factors Associated with Surgical Site Infections After Cardiac Surgery in a Taiwan Medical Center

Abstract: COPD is an independent underlying illness associated with SSI after cardiac surgery. Minimizing preoperative hospitalization and nosocomial infection, and awareness of cases presenting with relevant risk factors, are useful in reducing SSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 21 publications
1
17
1
3
Order By: Relevance
“…SSI was reported as 1.18% in the present study, but as 3% in the study by Lepelletier et al and 13.5% by Lee et al [23], [24]. Other studies have reported the rate of SSI to range from 3% to 10.4% [15], [25], [26], [27].…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…SSI was reported as 1.18% in the present study, but as 3% in the study by Lepelletier et al and 13.5% by Lee et al [23], [24]. Other studies have reported the rate of SSI to range from 3% to 10.4% [15], [25], [26], [27].…”
Section: Discussioncontrasting
confidence: 50%
“…According to studies conducted by Yamashita and Vardakas, diabetic patients are predisposed to a variety of infections, including nosocomial infections [28], [29]. According to Lee et al, however, diabetes is not a significant risk factor for SSI [24]. SSI in the present study was chiefly caused by E. coli (26.8%), followed by S. aureus and Klebsiella spp.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Preoperative risk factors include diabetes mellitus [1, 11-13, 59, 64, 71-85], obesity [1, 11, 59, 64, 71, 72, 74-77, 80-82, 84, 86-94], advanced age [75-77, 82, 90, 95, 96], COPD [59,81,84,91,[97][98][99], heart failure and left ventricular dysfunction [1,77,81,86,95,100], smoking [1,12,82,89], female sex [75,79,95,96,101], elevated serum creatinine level or patients undergoing haemodialysis [77,81,95,100], peripheral vascular disease [1,13,80], prolonged preoperative stay in hospital [59,78,101], emergent or urgent surgery [82,99,102].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Post-operative infections are typically defined to include all infections that develop within 30 d of surgery (within 365 d if the infection involves a prosthetic implant) [1]. The risk of SSI is especially high in patients who undergo emergency surgery because of inadequate pre-operative preparation, contaminated wounds, and underlying comorbidity [2][3][4][5][6]. Although a number of studies have addressed the incidence of specific types of post-operative infection (especially SSI) after selected elective procedures (e.g., total hip and knee replacement), there is little published information concerning the overall incidence of post-operative infection among patients who undergo major elective surgery in the United States.…”
mentioning
confidence: 99%